Teaching Out-Of-Field, Qualifications and Students’ Attitude Towards Christian Religious Studies in Secondary Schools in Calabar Municipality, Nigeria (Unilorin Journal of Lifelong Education, 2025)
In the modern age, the relevance of Christian Religious Studies (CRS) in secondary schools extends beyond spiritual growth; it fosters moral development, ethical reasoning, and societal values in students. However, many students exhibit a negative attitude towards CRS, often perceiving it as outdated or irrelevant in a contemporary world. This shift underscores the urgent need to revitalise interest and engagement in CRS. This research aims to examine teaching outof-field, qualifications and its influence on Senior Secondary School Two (SS2) students’ attitude towards Christian Religious Studies. The study adopted descriptive survey research design. Two hypotheses were formulated and tested at 0.05 level of significance. Simple random sampling technique was used to select 100 SS2 teachers and 343 SS2 students that constituted the sample. The instruments for data collection were Teaching Out-of-Field and Qualifications Questionnaire (TOFQQ) and Students’ Attitude Towards Christian Religious Studies Questionnaire (SATCRSQ). The reliability of the instrument was established using split-half method which yielded indices ranged from 0.73 and 0.87 respectively. Consequently, the instruments were found to be adequately reliable for use in the study. Analysis of variance (ANOVA) was used to analyse the collected and prepared data for all the hypotheses; at 0.5 level of significance. The result revealed that teaching out-of-field and qualifications had significant influence on students’ attitude towards Christian Religious Studies. It was recommended among others that educational institutions should prioritize hiring teachers with appropriate qualifications and expertise in Christian Religious Studies.